Why do consumers purchase biodegradable plastic? The impact of hedonics and environmental motivations on switching intention from synthetic to biodegradable plastic among the young consumers - Moshood, Taofeeq D.; Nawanir, Gusman; Fatimah, Mahmud; Fazeeda, Mohamad; Mohd Hanafiah, Ahmad; Airin, AbdulGhani (Elsevier, 2022)
Human concern for the environment has grown in tandem with recent economic development, particularly in emerging nations. This paradigm change has led Malaysians to pay more attention to synthetic plastics challenges, particularly in Malaysia. This study aims to determine the attitudes of young Malaysian consumers on the usage of biodegradable plastics to minimize the use of synthetic plastic in the country. Generally, two motivations—hedonic and environmental motivations toward switching intention from synthetic to biodegradable plastic among the young consumers were examined in the study. Environmental motivations (environmental concern, environmental knowledge), as well as hedonic motivations (adventurous spirit, novelty-seeking), are used in this study to broaden the theory of consumption value (TCV) into four additional factors that may positively impact the young consumer's attitude and increase switching intention towards biodegradable plastics. The data was collected utilizing an online survey approach and a standardized questionnaire. The data of 386 young Malaysian customers were analyzed using structural equation modelling (SEM) using SmartPLS 3. The study's significant findings indicated that hedonic motivations, environmental motivations, and attitudes all impact switching intentions toward biodegradable plastics. This study also found that attitude is a mediator between hedonic and environmental motivations regarding switching intentions. These findings might aid the government in developing a new policy that encourages residents to adopt biodegradable plastics while also lowering pollution.